PENINGKATAN HASIL BELAJAR MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF DIGITAL PADA TEMA 2 DI KELAS VI - Sisi Triani; Sandi Budiana; Hida Wahida Chusein (STKIP Subang, 2023)
This research aims to enhance learning outcomes by utilizing the Problem-Based Learning (PBL) model with the assistance of digital interactive media for Theme 2 in the sixth-grade primary school. The study employs a classroom action research design conducted over two cycles. Data collection methods include observing the performance of both teachers and students, as well as multiple-choice tests to measure learning outcomes. The data is analyzed using both quantitative and qualitative descriptive analysis techniques. The results of the classroom action research indicate that the teacher's performance in implementing PBL in the first cycle achieved a score of 60.5%. In the second cycle, there was an improvement to 80.5%, categorized as high performance with a high-quality interpretation. The learning outcomes In the first cycle, there were 8 out of 25 students who had achieved mastery, which accounts for 32%, with an average score of 63.2. In the second cycle, there was a significant improvement, with 21 out of 25 students reaching mastery, which is 84%, with an average score of 83.8. The conclusion of this research indicates that the Problem-Based Learning model with the support of digital interactive media can enhance the learning outcomes for Theme 2 in the sixth-grade curriculum, encompassing the subjects of Science and Indonesian Language.